Assessment of Intranasal Midazolam Administration with a Dose of 0.5mg/kg in Behavioral Management of Uncooperative Children - A - Eshghi; N Kavyani; R Mazaheri (Isfahan University of Medical Sciences, 2005)
Introduction. Some children show aggressive uncontrollable behavior during dental procedures, the only way to control this behavior is pharmacological methods such as conscious sedation. Recently intranasal administration of midazolam has been considered. The main goal of our study is to determine the effectiveness of intranasal administration of midazolam (in a does of 0.5 mg/kg) in behavioral management of uncooperative children.Methods and Materials. In this study 30 healthy, uncooperative children of 3 to 5 years old were evaluated. At the beginning of each session, we tried to use ordinary techniques of behavioral management in treatment of patients. In the case of unsatisfactory response intranasal midazolam was immediately used. To determine the affectivity of the drug, evaluation of child behavior before and after administration of midazolam was undertaken, using Houpt rating scale of general behavior.Results. A statistically significant difference was demonstrated in patients behavior before and after administration of intranasal midazolam (based on Houpt rating scale of general behavior). Thus we concluded that this drug is effective in sedation and reducing the anxiety of children under treatment.Discussion. Although the results are indicative of a positive effect of drug in sedating patients, this is not indicating that a child with a behavioral score of 1 or 2 of Houpt scale will be changed to a child with scores of 5 or 6 after administration of the drug. In fact this drug makes children more controllable in comparison to their previous condition and reduces their range of movement and crying so that dentist will be able to work in a relatively more suitable condition. Midazolam has the most effect in children who have a greater potential to cooperate and have a mild to moderate degree of anxiety.Key words. Intranasal midazolam, Pediatric dentistry, Conscious sedation.